1991
DOI: 10.1002/1097-0142(19910801)68:3<660::aid-cncr2820680337>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Are malignant melanoma patients at higher risk for a second cancer?

Abstract: This study tests whether malignant melanoma (MM) patients are at higher risk of having an unrelated second cancer by comparing the observed incidence of a second cancer in a given population of MM patients with the expected number in an age-matched and sex-matched group of healthy people followed for a similar period. The analysis was based on the person-years method in which the main consideration is the follow-up period after the diagnosis of MM. Of 370 patients with histologically confirmed MM, 27 (7.3%) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 20 publications
1
36
1
1
Order By: Relevance
“…The association between CM and other cancer is controversial, but clarification of these relations may lead to an improved understanding of aetiology. Several studies reporting an overall increased incidence of a second primary tumour among CM survivors have been small hospital-based case series or with short follow-up periods or included nonmelanoma skin cancer as a second primary (Adami et al, 1995;Swerdlow et al, 1995;Wassberg et al, 1996;Bhatia et al, 1999); the type of secondary tumour reported has been inconsistent (Gutman et al, 1991;Riou et al, 1995;McKenna et al, 2000).…”
mentioning
confidence: 99%
“…The association between CM and other cancer is controversial, but clarification of these relations may lead to an improved understanding of aetiology. Several studies reporting an overall increased incidence of a second primary tumour among CM survivors have been small hospital-based case series or with short follow-up periods or included nonmelanoma skin cancer as a second primary (Adami et al, 1995;Swerdlow et al, 1995;Wassberg et al, 1996;Bhatia et al, 1999); the type of secondary tumour reported has been inconsistent (Gutman et al, 1991;Riou et al, 1995;McKenna et al, 2000).…”
mentioning
confidence: 99%
“…However, the proportions of patients having a second primary cancer vary widely from 1.5% up to 20% and comparisons between the studies are difficult owing to differences in the length of follow-up (Fraser et al, 1971;Fletcher, 1973;Boland et al, 1976;Teppo et al, 1985;Tucker et al, 1985a;Gutman et al, 1991;Schallreuter et al, 1993). Previous studies suggest associations between malignant melanoma and an array of different specific types of cancer, such as tumours of the nervous system (Teppo et al, 1985;Tucker et al, 1985a), non-melanoma skin cancer (Fraser et al, 1971;Fletcher, 1973;Lindelof et al, 1991), Hodgkin's disease (Tucker et al, 1985b), non-Hodgkin's lymphoma (Teppo et al, 1985), leukaemia (Boland et al, 1976;Teppo et al, 1985), cancers of the breast (Boland et al, 1976;Schoenberg and Christine, 1980;Gutman et al, 1991;Schallreuter et al, 1993), ovary (Boland et al, 1976), endometrium (Tucker et al, 1985a), testis (Teppo et al, 1985) and tumours of the digestive tract (Bergman et al, 1990). Taken together, these earlier observations may fit into different hypotheses based on similar risk factors in malignant melanoma and other specific cancers.…”
mentioning
confidence: 99%
“…Among 370 patients diagnosed with malignant melanoma who were followed prospectively, a second primary cancer of breast later developed at a rate six times that expected (71), which suggests a common etiology for melanoma and breast cancer that may involve reduced melatonin. Melatonin has been reported to slow the growth of transplanted melanoma cells in athymic mice (72).…”
Section: Cancer Typesmentioning
confidence: 98%